2020
DOI: 10.4067/s0717-75182020000100006
|View full text |Cite
|
Sign up to set email alerts
|

El consumo de la polidextrosa previene la obesidad y sus comorbilidades en ratas alimentados con dieta hipercalórica

Abstract: RESUMEN El objetivo de este trabajo fue evaluar el efecto de las diferentes concentraciones de polidextrosa en la prevención de la obesidad y sus comorbilidades, en ratas alimentados con dieta hipercalórica. Se utilizaron ratas machos Wistar, repartidos en 4 grupos: Grupo control (HC) y 3 grupos que recibieron dieta hipercalórica con suplementación del 2%, 4% y 6% de polidextrosa (HC2%P, HC4%P y HC6%P respectivamente). La dieta hipercalórica utilizada fue la del tipo de cafetería para inducir la obesidad. Se m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Polydextrose is a polysaccharide synthesized by the polymerization of glucose. This sweetener is used in a wide range of baked products, confectionery, and beverages, since it provides texture and volume to food and has a low caloric value (1 kcal/g) and prebiotic properties [ 44 , 45 ]. Currently, the limit of consumption of polydextrose is not specified [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polydextrose is a polysaccharide synthesized by the polymerization of glucose. This sweetener is used in a wide range of baked products, confectionery, and beverages, since it provides texture and volume to food and has a low caloric value (1 kcal/g) and prebiotic properties [ 44 , 45 ]. Currently, the limit of consumption of polydextrose is not specified [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Polydextrose [44] "El consumo de la polidextrosa previene la obesidad y sus comorbilidades en ratas alimentados con dieta hypercaloric"…”
Section: United States Male and Female C57bl/6 M Miceunclassified
“…The product was protected from the development of Listeria monocytogenes bacteria by bacteria of the Staphylococcus carnosus strain. The proposed technology can be used in the food industry in the manufacture of raw meat products, which will significantly reduce the negative impact of sodium nitrite on human health Keywords: meat products; raw dried products; beef; pickling; bacterial preparation; sodium nitrite; quality and safety of finished products da Silva Souza et al, 2020;Macari et al, 2022). Extracts and ingredients from plants are an acceptable alternative to nitrite.…”
Section: Introductionmentioning
confidence: 99%
“…With a daily dose of 15 g of pectin for 2-3 weeks, bile excretion increases by more than 30%; cholesterol levels in the blood decrease by 13-15%. Modern researchers are also investigating the sorption properties of pectin substances from various sources(Wang et al, 2019).The paper(Souza et al, 2020) presented the results of a series of experiments involving laboratory animals and discovered that a diet with the addition of amaranth and dietary fiber (pectin and cellulose) reduces cholesterol in the blood serum and liver. It was found that pectin can bind and remove lipids from the body, and in an amount 4 times higher than its weight(Li et al, 2021 ).…”
mentioning
confidence: 99%